2006
DOI: 10.1289/ehp.8419
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Evaluation of Neonatal Exposure to 2,2′,4,4′,5-Pentabromodiphenyl Ether

Abstract: Exposure to the brominated flame retardant 2,2′,4,4′,5-pentabromodiphenyl ether (PBDE-99) during the brain growth spurt disrupts normal brain development in mice and results in disturbed spontaneous behavior in adulthood. The neurodevelopmental toxicity of PBDE-99 has been reported to affect the cholinergic and catecholaminergic systems. In this study we use a proteomics approach to study the early effect of PBDE-99 in two distinct regions of the neonatal mouse brain, the striatum and the hippocampus. A single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 40 publications
2
52
0
Order By: Relevance
“…In mice, the increased expression of GAP-43 protein (1.25-fold) was found in developing mouse brains after 24 h exposure to BDE-99 (12 mg/kg body weight). 42 Following neonatal exposure to BDE-209 (20.1 mg/ kg body) in mice, GAP-43 was significantly increased in the hippocampus after 7 days. 43 However, neonatal exposure to BDE-203 and -206 (21 μmol/kg) for 24 h in mice during rapid brain growth and development did not affect GAP-43.…”
Section: Environmental Science and Technologymentioning
confidence: 94%
“…In mice, the increased expression of GAP-43 protein (1.25-fold) was found in developing mouse brains after 24 h exposure to BDE-99 (12 mg/kg body weight). 42 Following neonatal exposure to BDE-209 (20.1 mg/ kg body) in mice, GAP-43 was significantly increased in the hippocampus after 7 days. 43 However, neonatal exposure to BDE-203 and -206 (21 μmol/kg) for 24 h in mice during rapid brain growth and development did not affect GAP-43.…”
Section: Environmental Science and Technologymentioning
confidence: 94%
“…A decrease of CaMKII, in addition to decreases in the levels of brain derived neurotrophic factor (BDNF) and of Gap-43 (neuromodulin) were also found on PND 10 in mice exposed to BDE-209 on PND 3 (Viberg et al 2007b). A proteomic analysis of hippocampus and striatum of mice 24 h after the administration of BDE-99 (12 mg/ kg on PND 10) revealed changes in the levels of a number of proteins (Alm et al 2006). Among these, Gap-43, which was increased in the striatum, and stathmin, which was decreased.…”
Section: Biochemical Studies Following In Vivo Developmental Exposurementioning
confidence: 99%
“…Both are substrates of protein kinase C (PKC), which has been shown to be affected by PBDEs in vitro (Madia et al 2004;. Various enolases, as well as alpha synuclein were also increased in the hippocampus (Alm et al 2006). In a study in rats, prenatal exposure to BDE-99 was shown to increase the activity of the glutamate -nitric oxide-cGMP pathway, as assessed by microdialysis (Llansola et al 2007).…”
Section: Biochemical Studies Following In Vivo Developmental Exposurementioning
confidence: 99%
“…Although there have been numerous statistical analyses performed with DIGE investigations, there is presently no consensus strategy for identifying differential proteins. 31,34,35 We present here an alternative that is simple yet robust for minimizing false-positives.…”
Section: A Threementioning
confidence: 99%
“…FDR is used extensively in microarray transcript profiling experimentation and has also been used by a few groups to characterize proteome data sets. 9,31,34,35 In this paper, we applied FDR for selection of deferentially expressed spots. FDR is a statistical procedure that is effective in correcting for multiple simultaneous hypothesis tests.…”
Section: A Threementioning
confidence: 99%